2020
DOI: 10.21203/rs.3.rs-17022/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using machine learning methods to predict physical activity types with Apple Watch and Fitbit data using indirect calorimetry as the criterion.

Abstract: Background There is considerable promise for using commercial wearable devices for measuring physical activity at the population level. The objective of this study was to examine whether commercial wearable devices could accurately predict lying, sitting, and intensity level of other activities in a lab-based protocol. Methods We recruited a convenience sample of 49 participants (23 men and 26 women) to wear three devices, an Apple Watch Series 2, a Fitbit Charge HR2, and and iPhone 6S. Participants completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Like the MHR outcomes, when comparing MEE on both the AW7 and the PARVO, it also shows that there is no difference between the variables, which is in agreement with previously performed studies 21,22,25 . Contrary to the results MEE found, most of the studies (performed with past models) do not suggest the MEE of AW to be valid as the measurement errors are too large [6][7][8][9]13,19,23,34 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Like the MHR outcomes, when comparing MEE on both the AW7 and the PARVO, it also shows that there is no difference between the variables, which is in agreement with previously performed studies 21,22,25 . Contrary to the results MEE found, most of the studies (performed with past models) do not suggest the MEE of AW to be valid as the measurement errors are too large [6][7][8][9]13,19,23,34 .…”
Section: Discussionsupporting
confidence: 90%
“…However, the error rate was still too high to consider the AW a valid instrument for measuring one's MEE during exercise [6][7][8][9]13,17,19,23 . On the contrary, studies indicated that the AW series 1 and 2 are valid measurements of MEE during running on the treadmill when compared to the indirect calorimetry 25,26 . It is well supported by previous findings that the MEE estimations of AW have poor accuracy, however, it is important to note that there has only been research done with Apple Watches up to series 6.…”
Section: Energy Expenditure Estimations Of Apple Watchesmentioning
confidence: 95%
See 2 more Smart Citations
“…The study selected 42 students from the Faculty of Computer and Mathematical Sciences, Universiti Teknologi MARA Kelantan as the target group. Convenience sampling (Fuller et al, 2020;Jin et al, 2019) of the target population, namely students who were involved with group projects in a PBL environment was used in this research. The data collected, which comprised 150 comments from the 42 students who were using WhatsApp messages was used to perform the sentiment analysis.…”
Section: Exploratory Sequential Research Methods To Obtain Student Feedback During the Mcomentioning
confidence: 99%